Analysis and verification on space probe performance of 2-D spectrum estimation algorithm - Ting LI (Dianxin kexue)
According to the analysis requirement of the space probe performance of 2-D spectrum estimation algorithm,a brief introduction of the 2-D spectrum estimation algorithms was given in the view of calculating speed,calculating volume,stability,accuracy and practical application.These algorithms were the spectrum estimation algorithms of the 2-D MUSIC,the 2-D interference and the 2-D MEMP with the L-shaped array.The estimation performance of the algorithms were analyzed by simulations,the angle root mean square error of three algorithms were compared and analyzed.Simulation results show that the performance of the 2-D MEMP is the best,the performance of the 2-D interference algorithm is the worst,and the performance of the 2-D MUSIC is moderate.Meanwhile,the experimental scene was constructed,and the space probe performance of the 2-D spectrum estimation algorithm was analyzed by real data.The experimental results were consistent with the simulation results.Based on this,the 2-D MEMP algorithm may be further applied in the radar and TT＆C system.